O processo de criação do telejornal Fantástico nas matérias com enfoque em personagens - Abe, Luciano Koji (2016)
This dissertation analyzes the creative process of Rede Globo's Sunday news broadcast, Fantástico, produced during the years 2014-2015, focusing on similarities and differen-ces between film and television, as they pertain to protagonists and the hero's journey. The research investigates the program's creative process through the examination of fictional and documentary film resources, such as studying scripts and editing techni-ques. As with cinema, television, which was popularized in the 1950s with the aim of educating and entertaining viewers, was based on the creativity of the invention of the Lumière brothers. The text of the first chapter provides a brief history of Fantástico, with focus on the delimitation of the research, up to the present newsroom-studio for-mat, at the same time increasing the diversity of programming and the number of chan-nels, especially with advent of cable TV. The second chapter addresses the script wri-ting procedures in the construction of characters. This part of the dissertation, based on the construction of life stories of individuals or social groups, attempts to understand the resources that the television news report use to stimulate the viewer's emotions. The final chapter deals with audiovisual resources in building characters and analyzes some reports. The text of this chapter devotes greater treatment to the image in the post-modern world and editing through rhythm and sensations. The dissertation is based on the theories of Edgar Morin and Cecilia Almeida Salles, with the importance of theories of creation as network and cultural influences to think about the production of a news-cast